CERN hadron sources: status and innovation overview. Issue 1 (1st April 2022) - Wenander, F
Abstract: The CERN accelerator complex is served by several different types of hadron sources, producing both high- and low-intensity negative H - beams, highly charged positive stable ions, but also transforming low-charge radioactive ions to higher charges before post-acceleration. Apart from the operational sources, research and development is carried out at dedicated test stands for H - production and pre-acceleration, ECRIS oven experiments and general EBIS development. In this paper, we will report on the performance and the latest development related to the sources. Efforts to enhance the theoretical understanding of the source physics will be briefly reviewed.